2011
DOI: 10.1248/bpb.34.1849
|View full text |Cite
|
Sign up to set email alerts
|

Mate Tea (Ilex paraguariensis) Promotes Satiety and Body Weight Lowering in Mice: Involvement of Glucagon-Like Peptide-1

Abstract: Ilex paraguariensis St. HILL (Aquifoliaceae) leaves, popularly known as maté (mate), yerba-mate, or erva-mate, are used in the preparation of several types of tea, beverage, and soft drink in South America. Mate trees grow naturally and have been cultivated in southern Brazil, Argentina, and Paraguay, and the popularity of its preparations is increasing worldwide, particularly in North America and Europe.1) Mate has central nervous system-stimulant properties attributed to its content of methylxanthine alkaloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 24 publications
(27 reference statements)
0
41
0
3
Order By: Relevance
“…Previously, we have reported that various constituents such as acylated quinic acids, flavonoids, and terpenoids from natural medicines and medicinal foods inhibited aldose reductase inhibitory effect. 48,49) were examined for the structure-activity relationship study (Fig. 3, Table 2).…”
mentioning
confidence: 99%
“…Previously, we have reported that various constituents such as acylated quinic acids, flavonoids, and terpenoids from natural medicines and medicinal foods inhibited aldose reductase inhibitory effect. 48,49) were examined for the structure-activity relationship study (Fig. 3, Table 2).…”
mentioning
confidence: 99%
“…For the active ghrelin ELISA, 1 N hydrogen chloride was added to the samples immediately after the plasma separation to achieve a final concentration of 0.1 N, as described previously [11]. The plasma active GLP-1 levels were measured by ELISA (mouse active GLP-1 ELISA kit; Shibayagi Inc., Gunma, Japan) [12, 13]. …”
Section: Methodsmentioning
confidence: 99%
“…비 만에 대한 효과는 열발생효과(thermogenesis) 6) , 지방대 사증진 효과 7) , 지방세포 크기를 줄이는 효과 8) , GLP-1(glucagon-like peptide-1)과 렙틴 분비의 증가를 통한 식욕억제 효과 9) , 그리고 지질생성(adipogenesis)과 관련 된 유전자의 발현을 조절하는 효과 에 발표되었다. 반면에 마테가 topoisomerase Ⅱ 활동의 억제를 통해 구강암 13) 과 사람의 간암세포 (HepG2) 14) 의 증식을 막는다는 in vitro 연구들도 있어 발 암 가능성에 대해 논쟁이 많다.…”
Section: 서론unclassified